2017
DOI: 10.1177/1687814016688859
|View full text |Cite
|
Sign up to set email alerts
|

A novel under-actuated bionic hand and its grasping stability analysis

Abstract: This article presents a novel under-actuated robot hand, which has a thumb and two cooperative fingers. The thumb has two joints with 2 degrees of freedom driven by one motor. Each of the other two fingers has the same mechanism structure with the thumb and forms a cooperative mechanism, which is driven by only one motor with 4 degrees of freedom in total. All the under-actuated fingers are designed with the transmission mechanisms based on a kind of mechanism combined with the linkage mechanism and the passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The articles [18], [20], [22], [23], [26], [29] exhibit a single degree of freedom and are unable to grasp objects with irregular shapes, a situation addressed in this article by employing the non-linked doubletendon arrangement. On the other hand, the articles [19], [27], [28], [30]- [32] feature a mechanical finger design with more than one degree of freedom, enabling them to grasp objects with irregular shapes. However, they lack a closed-loop control strategy, an aspect that is considered in the present article.…”
Section: Performance Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles [18], [20], [22], [23], [26], [29] exhibit a single degree of freedom and are unable to grasp objects with irregular shapes, a situation addressed in this article by employing the non-linked doubletendon arrangement. On the other hand, the articles [19], [27], [28], [30]- [32] feature a mechanical finger design with more than one degree of freedom, enabling them to grasp objects with irregular shapes. However, they lack a closed-loop control strategy, an aspect that is considered in the present article.…”
Section: Performance Of the Resultsmentioning
confidence: 99%
“…In [17] a hand controlled by various types of signals is presented, these are encephalographic, myoelectric, voice and gestures, the project provides a comprehensive explanation of the methods used to acquire the different signals; however, to move the hand, a control law is not used, that is, it is an open loop system. In [18], [19], it was also observed that they use myoelectric sensors as triggers of the control action. In [20]- [23], a hand prototype with five fingers divided into three parts (phalanges), joined by a small pulleys system is presented, in which, to perform the bending movement a direct current motor is used at the base, which acts on a wire (or cable) which runs through the inside of the finger and connects to the distal phalanx.…”
Section: Introductionmentioning
confidence: 99%
“…The derived grasper can increase its robustness against external force perturbations. The UnderActuated UA finger [45] presented in the second row of Table 5 uses as the driving input the mechanical torque applied to link 1 (it does not have the interchangeability that characterizes the patent [43]). A and B are the MCP and PIP joints and once the link 3 is in contact with the object, the torsion spring 5 allows under actuation to be activated (in this case BE and ED are collinear).…”
Section: Referencementioning
confidence: 99%
“…Others adopted flexible fingers, fingers with flexible surfaces as an interface for grasping, or fingers with flexible joints [4][5][6][7][8][9][10]. Moreover, under-actuated mechanisms have also been employed to achieve safe and stable grasping [11][12][13][14][15][16][17][18]. While these approaches have proved effective, the levels of control and accuracy are still far from the biomimicry of natural grasping.…”
Section: Introductionmentioning
confidence: 99%